The role of corporate strategy in transfer pricing: The moderating effect of bonus mechanisms on performance management - Mardjono, Enny Susilowati; Yang, Yi-Fang; Nehayati, Nela (Universitas Muhammadiyah Yogyakarta, Indonesia, 2025)
Research aims: This study seeks to prove empirical evidence regarding the moderating effect of bonus mechanisms on fiscal optimization and tunnelling incentives on the Transfer Pricing relationship.Design/Methodology/Approach: The study uses a quantitative approach with a hypothesis-testing design. The data used is natural resource sector companies listed on the Indonesian Stock Exchange (IDX) in the 2021 – 2023 period. The final sample consists of 152 observations that meet the selection criteria.Research findings: The results showed that the Tunneling Incentive has an influence on Transfer Pricing, and Fiscal Optimization does not influence Transfer Pricing. The Bonus Mechanism does not strengthen the Effect of the Tunneling Incentive on Transfer Pricing. The Bonus Mechanism enhances the effect of fiscal optimization on transfer pricing. This research shows that the ownership factor (Tunneling Incentive) plays an important role in Transfer Pricing decisions rather than Tax strategy (Fiscal Optimization). In addition, the Bonus Mechanism moderate the relationship between Fiscal Optimization and Transfer Pricing. However, the Bonus Mechanism does not moderate the relationship between Tunneling Incentive and Transfer pricing. Theoretical contribution/ Originality: The originality of this research is based on the moderating results of the bonus mechanism, which strengthens the effect of Fiscal Optimization on transfer pricing compared to previous studies.Practitioner/Policy implications: The practical implications of this study suggest that companies need to be more transparent in Transfer Pricing policies, regulators should increase supervision against Tunneling practices, and investors and auditors should be more wary of companies with concentrated ownership structures.Research limitations/Implications: The limitation of this research is the research scope, which is just in the resource sector used in this research. The study does not account for potential changes in tax regulations or corporate governance laws that could impact the results over time.